Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Siswa pada materi benda tunggal dan campuran Kelas V SDN 62 Banda Aceh - Wirdhatul Aini; Bukhari Bukhari; Suci Fitriani (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the effect of the STAD Type Cooperative Learning Model on student learning outcomes in single and mixed materials for fifth-grade students at SDN 62 Banda Aceh. The method in this study is a quantitative methodology, with the Posttest model on control group design. The population in this observation is the students of SDN 62 Banda Aceh as many as 62 students in class V. The technique of collecting information is carried out by testing in the form of multiple choice questions totaling 10 items. The procedure for checking information is by applying a non-parametric statistical test, namely the Mann-Whitney test. According to the estimation results of the Mann-Whitney test on the overall student data, it appears that the calculated value of Z is -3.618. This means that the cumulative probability value of -3.618 (0.05), then H1 is recognized, and H0 is rejected. Then the level of significance (sig) is 0.00 0.05. Thus, it means that there is a comparison between student learning outcomes when applying the STAD type learning model, or it can be stated that there is an effect of the STAD type student learning model on the learning outcomes of fifth-grade students at SDN 62 Banda Aceh.